The Influence Of Workload, Work-Life Balance And Psychological Contracts On Employee Job Satisfaction Case Study: PT. PLN (Persero) Transmission Implementation Unit Makassar - Safirah Era Lestari Abrianti; Muhammad Ichwan Musa; Rezky Amalia Hamka (International Journal of Education Management and Religion, 2026)
This study aims to determine the effect of workload, work-life balance, and psychological contract on employee job satisfaction at PT. PLN (Persero) Makassar Transmission Implementation Unit. This study uses a quantitative approach with a survey method. Data was collected through a questionnaires distributed to all 56 employees. The data collection techniques used were observation, interviews, and questionnaires. The data analysis technique used was multiple linear regression with SPSS Software. The results of the study indicate that partially, workload has a negative and significant effect on employee job satisfaction, while work-life balance and psychological contracts have a positive and significant effect on employee job satisfaction. Simultaneously, workload, work-life balance, and psychological contracts have a significant effect on employee job satisfaction at PT. PLN (Persero) Makassar Transmission Implementation Unit.